Study on Temperature Field Massive Concrete in Early Age Based on Temperature Influence Factor - Min Zhang; Xianhua Yao; Junfeng Guan; Lielie Li (Advances in Civil Engineering)
In order to solve the problem of insufficient accuracy of early temperature field caused by the change of hydration rate under different temperatures, the theoretical formula of finite element calculation based on temperature influence factor is put forward and then the theory is tested. On this basis of this theory, the early temperature field of a RCC dam is numerically simulated and the variation law of concrete hydration rate under different temperatures is studied. The numerical simulation results are compared with the results without considering the temperature effect and the measured temperature data. The results show that the theoretical results are in agreement with the measured temperature data, and the accuracy and applicability of the theoretical formula are proved.